Institutions and the support for market reforms - Irina Denisova (IZA World of Labor, 2016)
Economic self-interest and social considerations are the key determinants of public support for market reforms in transition countries. However, political strategies that rely mainly on public support for pushing through economic reforms have limited relevance if the prevailing institutional environment is weak or corrupt. Poor governance and under-developed democracy significantly reduce the level of support. A good institutional framework allows the potential gains from reforms to be realized in a beneficial way, while corruption and poor governance deny the prospect of gains for individuals and for society.
Keywords: A13; C81; L33; P36; 330; public opinion; market reforms; privatization revision; legitimacy of property rights; transition countries